The use of bone marrow derived mesenchymal stem cell for cornea regeneration in rabbit model - Then K.Y.; Azlina M.; Ropilah A.R.; Ruszymah B.H.I.; Rohaina C.M.; Ng M.H. (Kugler Publications, 2024)
Indexed by SCOPUS